Medication Adherence of Persons with Type 2 Diabetes in Malaysia : A Scoping Review and Meta-Analysis - Teng, Cheong Lieng; Chan, Chun Wai; Wong, Pei Se (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objective. This is a scoping review of Malaysian scientific studies on medication adherence among persons with type 2 diabetes mellitus (T2DM). Methodology. We conducted a bibliographic search of PubMed, Scopus and Google Scholar using the following keywords: “medication adherence,” “drug compliance,” “DMTAC” and “Malaysia.” The search covered all publications up to 31 December 2021. Eligible articles were original studies conducted in Malaysia that measured or quantified medication adherence among persons with T2DM. Results. We identified 64 eligible studies published between 2008 to 2021. Most studies included patients with T2DM in ambulatory facilities. Five studies were qualitative research. The quantitative research publications included clinical trials, and cross-sectional, validation, retrospective and prospective cohort studies. Thirty-eight studies used medication adherence scales. The Morisky Medication Adherence Scale (MMAS-8, used in 20 studies) and Malaysian Medication Adherence Scale (MALMAS, used in 6 studies) were the most commonly used tools. There were six validation studies with four medication adherence scales. A meta-analysis of 10 studies using MMAS-8 or MALMAS revealed that the pooled prevalence of low medication adherence is 34.2% (95% CI: 27.4 to 41.2, random effects model). Eighteen publications evaluated various aspects of the Diabetes Medication Therapy Adherence Clinics (DMTAC). Conclusion. This scoping review documented extensive research on medication adherence among persons with diabetes in Malaysia. The quantitative meta-analysis showed a pooled low medication adherence rate.